The effects of maternal employment on mother's representations of mother-child relationships in a changing European society - Mertan, Biran E.; Balleyguier-Boulanger, Geneviève (Presses Universitaires de France, 2008)
The current study examined the effects of maternal employment on mother-child relationships. 156 mothers of toddlers aged 12 to 36 months had to fill a questionnaire related to their reciprocal relationship with their child. Among them, eighty-seven were employed and 69 full-time mothers. Results show that employed mothers appeared to be especially affectionate towards their children compared to the mothers at home. By contrast, they evaluate significantly more often their child as showing separation anxiety. Full-time mothers appeared to be more concerned with educational matters and evaluated more often their child as obedient compared to the employed mothers. Results are discussed in terms of developmental risk factor of non-parental care.
Quelques conséquences du travail des mères sur leurs représentations des relations mère-enfant dans une société européenne en mutation
Keywords: Changing society; Maternal employment; Mother/child relationship